3-tert-Butyl-1-(3-nitrophenyl)-1H-pyrazol-5-amine - Hernández-Ortega, Simón (International Union of Crystallography, 2012)
In the title compound, C(13)H(16)N(4)O(2), the pyrazole ring forms a dihedral angle of 50.61 (6)° with the 3-nitro-phenyl ring. The plane of the nitro group is twisted by 6.8 (7)° out of the plane of the phenyl ring. In the crystal, the molecules are linked by N—H⋯N and N—H⋯O hydrogen bonds, forming sheets in the bc plane. In addition, a weak C—H⋯N interaction is observed.